Control of heat transfer and fluid flow using a triangular bar in heated blocks located in a channel - Öztop, Hakan Fehmi; Varol, Yasin; Alnak, Dogan E. (Pergamon-Elsevier Science Ltd, 2009)
Control of laminar, two-dimensional, steady forced convection heat transfer and fluid flow in an isothermally heated blocks located in a channel was analyzed numerically. The channel had three blocks attached on its bottom wall. The cooling air entered the channel with uniform velocity. A triangular cross-sectional bar was used as a control element. Both the top wall of the channel and the bar were isothermal. The bar was located in two different points in the y-direction and these parameters were tested at three different Reynolds numbers ranging between (400 <= Re <= 1300). Results were also compared for no triangle case. It was obtained that insertion of a triangular cross-sectional bar enhanced the heat transfer for all Reynolds numbers and the best heat transfer was observed for the position of the bar with y = 3.5. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Heat transfer; Triangular bar; Heated block